Childhood trauma and problematic internet use: A meta-analysis based on students in mainland China - Wang, Xiaotong; Li, Dexian; Li, Shunyu (Frontiers in Psychology, 2023)
The aim of this study is to explore the relationship between childhood trauma and problematic Internet use, and the effects of some moderating variables on both for students in Mainland China.Among the papers included in the meta-analysis in this study, 31 papers reflected the relationship between childhood trauma and problematic Internet use, involving 52,503 subjects, and the sample size ranged from 388 to 16,130. This relationship between childhood trauma and problematic Internet use can be considered as a moderate correlation(r=.281, 95%CI[.221, .338], p＜0.001). The results showed that the relationship between childhood trauma and problematic Internet use was affected by different problematic Internet use measures. Meanwhile, meta-regression demonstrated that the relationship between childhood trauma and problematic Internet use was moderated by survey’s year. Specifically, the correlation coefficient between childhood trauma and problematic Internet use also increases with increasing year. However, the relationship between childhood trauma and problematic Internet use was not affected by the region, grade, childhood trauma measures, publication source. In order to reduce problematic Internet use, corresponding prevention and intervention measures should be taken.